Classification of Main Faults in the Production Process of Extruded Aluminium Profiles - Al-jabbouli, Hasan; Koç, Ebubekir; Akça, Yaşar (İstanbul Gelişim Üniversitesi, 2015)
Aluminium use has been rising steadily in recent decades. Several different industries are adapting it since its light weight, doable structure and robustness. Aluminium manufacturing runs in three ways; namely: (1) cascading, (2) extrusion and (3) drawing. Extrusion process is used to form aluminium in profiles which is one of the main semi/final-products for many industries. Although profiles production runs smoothly and easily most often, there are a number of repeated faults which might occurs during the extrusion process and some distinct patterns of faults and defects can be seen on the surface of the produced profiles. This paper describes the main types of these faults and defects and suggested solutions to avoid them based on 24 months of observations for the production process at three different extrusion machines in two different aluminium profiles manufacturing plants. The main aim of this study is to classify these faults and defects to help manufacturer to control and to avoid them or at least to minimize their occurrences by optimising quality control systems.
Keywords: Aluminium Extruded Profiles; Defects; Scratches; Faults; Aluminium Production